PENGARUH RANCANGAN BARISAN DAN PERIODE PANGKAS TERHADAP BIOMASA DAN HASIL UNSUR HARA TITONIA (Tithonia diversifolia) PADA ULTISOL - Asmar Asmar; Oktanis Emalinda; Dicky Hadi Vendra (Jurnal Solum, 2012)
A field research about cultivating tithonia (Tithonia divesifolia) was aimed to determine the best row design and trimming period to produce high biomass and nutrient content of tithonia in Ultisol. The research was conducted in Andalas University Experiment Station and Laboratory of Research Center for Utilization of Nuclear Science and Technology (P3IN) Universitas Andalas Limau Manis Padang. The research consisted of 2 factors, row design for tithonia cultivation at farming site (R) (R1=alley fence, 1 m width times 5 m distance; R2 = 1 m width as a fence for farming site 10 m x 10 m area) as the main plot and trim period (U) (U1=trimming every 2 month, U2=trimming every 4 months), at 3 blocks The results showed that both row designs gave the same performance in terms of producing biomass and plant nutrients (N,P,K,Ca,Mg). The best trimming period was found under U1. Tithonia cultivation as R1 combined with trimming period (U1) yielded approximately 2.2 ton dry matter/ha, 62.82 kg N/ha; 17.67 kg P/ha; 81.06 kg K/ha 13.35 kg Ca/ha and 5.47kg Mg/ha. Both row designs with trimming period every 2 months could be recommended to cultivate tithonia in Ultisol.Key Words: Tithonia diversifolia cultivation, trim period, Ultisol